A Retrospective Real-World Observational Study Assessing the Evolution of Bisacodyl Prescriptions in Patients with Constipation During Long-Term Treatment - Michel Bouchoucha; Caroline Amand; Beatrice Bois De Fer; Robert Lange (Adis, Springer Healthcare, 2023)
Abstract Background Potential habituation could be a safety concern associated with the long-term use of bisacodyl in patients with constipation. Objective In this study, we evaluated whether patients with constipation who require long-term treatment with bisacodyl will remain on a stable dose when treated for ≥ 28 days. Methods In this retrospective, population-based, observational cohort study, electronic medical record data of adult patients with constipation between January 1, 2011, and December 31, 2019, were collected from The Health Improvement Network French database. Total bisacodyl exposure during the long-term (≥ 28 days) and follow-up (12 months) periods was evaluated. The primary endpoint was the dose change status of bisacodyl during the follow-up period from the initial dose in the long-term cohort. Results Out of 5725 bisacodyl users in the database, 218 patients qualified to be part of the long-term cohort. A total of 166 (76.1%), 37 (17%), and 15 (6.9%) patients were initiated on bisacodyl at 5, 7.5, and 10 mg, respectively. During the follow-up, most (94%) of the patients remained on the same dose as initially prescribed for the first year. In contrast, only seven (3.2%) patients had their dose increased (from the initial prescribed dose of 5 mg), and the remaining six (2.8%) patients decreased their dose (four patients from the 7.5 mg group and two from the 10 mg group). Conclusion Bisacodyl can be prescribed at a stable dose for > 28 days as most patients remained on their initial prescribed dose during the follow-up period. No signs of habituation were observed in this real-world study.